An Analysis of Studentsâ€™ Errors on Storytelling Presentation in English Department, University of Dehasen Bengkulu - Sembiring, Lina Tri Astuty Beru (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2017)
This study was aimed to investigate the kinds of grammatical errors made by English Foreign language learners in presenting storytelling. Since the students were learners who came from a multilingual community, the errors they made were affected by the structure of their daily language form. In this study, students were required to produce a story based on the book â€œFrog where are youâ€ written by Marcel Mayer. This book contains 29 pictures which tell a story without any texts on it. The writer then audiotaped studentsâ€™ storytelling and then made a transcription. The storytelling presentations of 5 students of English Departement of Universitas Dehasen Bengkulu were investigated by using the surface structure taxonomy of errors namely, misformation, misordering, addition, and omission. Findings indicated that omission was the highest kind of errors accounted on the total grammatical errors made by the students. It then followed by misformation, addition and also misordering.